Effect of Water-Cement Ratio on Pore Structure and Strength of Foam Concrete - Zhongwei Liu; Kang Zhao; Chi Hu; Yufei Tang (Advances in Materials Science and Engineering)
Foam concrete with different dry densities (400, 500, 600, 700, and 800 kg/m3) was prepared from ordinary Portland cement (P.O.42.5R) and vegetable protein foaming agent by adjusting the water-cement ratio through the physical foaming method. The performance of the cement paste adopted, as well as the structure and distribution of air pores, was characterized by a rheometer, scanning electron microscope, vacuum water saturation instrument, and image analysis software. Effects of the water-cement ratio on the relative viscosity of the cement paste, as well as pore structure and strength of the hardened foam concrete, were discussed. Results showed that water-cement ratio can influence the size, distribution, and connectivity of pores in foam concrete. The compressive strength of the foam concrete showed an inverted V-shaped variation law with the increase in water-cement ratio.